Pengembangan Gerak Tari Tradisional Batak Toba Berdasarkan Elemen Gerak - Martozet Martozet; Nurwani Nurwani; Yusnizar Heniwaty; Frisdo Ekardo (Gesture: Jurnal Seni Tari, 2026)
In creating dance, the creator or choreographer will be faced with creative work in determining the composition of movements that will be arranged based on the choreographic structure. Development can be done in the studio by developing through movement elements. This study uses a qualitative descriptive approach, which focuses on the development of movements based on movement elements, namely energy, space, and time based on four Toba Batak traditional dance motifs, namely Mandenggal, Embas, Somba Situan Natorop, and Padao Mara. This study uses the theory of movement stimuli by La Meri, where there are five stimuli in dance creation and movement theory by Jacqueline Smith, including energy, space, and time. The results of the study explain that the results of the development of movements through movement elements, namely energy, space, and time for the four Toba Batak traditional dance motifs of Mandenggal, Embas, Somba Situan Natorop, and Padao Mara, have produced new forms and colors of movement. The results of the development of these three elements provide a constructive creative experience and the choreographer has succeeded in obtaining various new, even unique, motif forms.